Workflow for efficiently isolating microspore cultures of different rice genotypes by optimizing the callus induction medium - Chen, Zhiwei; Guo, Guimei; Zhang, Shuwei; He, Ting; Feng, Shiji; Liu, Chenghong; Wang, Yu; Zhou, Longhua (Frontiers in Plant Science, 2025)
As one of the most important staple foods in the world, rice plays a key role in global food security. Doubled haploid technology based on isolated microspore culture can shorten the time taken for rice breeding programs. However, this technology still faces many problems, such as genotypic dependency, low culture efficiency, and a shortage of skilled workers. In this study, 15 rice genotypes, comprising 12 japonica genotypes and 3 indica genotypes, were randomly selected for microspore culture research, and the effects of different callus induction media (CIMs) on callus induction were compared and the related plant regenerations were also shown. The results showed that maltose was the optimal carbon source and the CIM III was the best for callus induction by comparing the number of rice genotypes that could be induced to form calli and the callus yields. For plant differentiation, 12 of the 14 rice genotypes regenerated green seedlings, all of which were japonica rice genotypes. Ploidy identification showed that the spontaneous doubling rate of regenerated seedlings from isolated microspore cultures ranged from 14.3 to 98%, which was higher than that observed in anther cultures. In conclusion, this study established an isolated microspore culture method that is suitable for different rice genotypes, providing more options for using doubled haploid technology in rice.